Identifying top researchers in highly metricized academia: two discursive strategies of senior officials in Poland. Issue 2 (4th March 2023) - Krawczyk, Stanisław; Szadkowski, Krystian; Kulczycki, Emanuel
ABSTRACT: Our study examines the discursive construction of academic subjectivity within the context of the current reforms of academia, driven by the forces of economization and metricization. We focus in particular on the construction of two models of top researchers. Drawing from the theory of Pierre Bourdieu, we call these models 'autonomous' and 'heteronomous'. We investigate 22 in-depth interviews and construct the ideal types of two discursive strategies that Polish senior academic officials use to build the respective models. We also inspect the empirical signs of a tension between those strategies, as well as three ways to deal with limited levels of this tension: using disclaimers, leaving the tension unaddressed, and attempting to reconcile the two strategies. Further, we demonstrate how a high-level tension results in a discursive split, which can be hypothetically linked to the divided habitus of some Polish academics.